Effect of solvent type and high pressure treatment on the extraction of Gomphrena globosa L. bioactive compounds - Fernandes, Luana (2018)
The present study aimed to compare the influence of different extraction solvents (water, methanol, water:acetone (6:4, v/v)), methods (heating (37 °C, 30 min) or high pressure (HP) (300 or 500 MPa) and extraction time (7.5 or 15 min)) on flavonoids, hydrolysable tannins and antioxidant activity (Total Reducing Capacity (TRC), DPPH Free Radical Scavenging Activity and Reducing Power) of Gomphrena globosa L. flower extracts. The water:acetone extracts obtained by heating had the highest values of flavonoids, hydrolysable tannins and antioxidant activity. When applying HP, variable results were obtained. Still, the application of HP to water allowed to extract more hydrolysable tannins, as well as to obtain extracts with higher antioxidant activity than with heating, but no significant alterations were observed with methanol. In conclusion, both solvent and extraction method influence the content of bioactive compounds, being HP treatment a promising method to obtain enriched aqueous extracts in line with the principles of green-chemistry.